2004
DOI: 10.1177/1350508404047253
|View full text |Cite
|
Sign up to set email alerts
|

The Cocoon—A Traveling Space

Abstract: As a graduation project at a design school in Stockholm, a piece of furniture to be used for retreats in the public space was exhibited. It was named 'The Cocoon' and was a reclining chair covered with a bubble-like construction made out of cloth and steel. The exhibition was a starting point for a number of journeys. In the years to come, the Cocoon reached museums, exhibition halls, newspapers and magazines throughout the world. In this article, we track the travels and illustrate the transformations of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 9 publications
(7 reference statements)
0
19
0
Order By: Relevance
“…We suggest that the appropriation of Lefebvre in organization studies can by and large be inserted in this third stream of readings of Lefebvre. The first tranch of organization studies papers to make reference to Lefebvre's triad, which we will further discuss below, appeared only in Dobers and Strannegård, 2004;.…”
Section: Lefebvre's Influencementioning
confidence: 99%
“…We suggest that the appropriation of Lefebvre in organization studies can by and large be inserted in this third stream of readings of Lefebvre. The first tranch of organization studies papers to make reference to Lefebvre's triad, which we will further discuss below, appeared only in Dobers and Strannegård, 2004;.…”
Section: Lefebvre's Influencementioning
confidence: 99%
“…In their attempts to better understand how organizational spaces are conceptualized and struggled for, organization scholars have drawn heavily on Lefebvre's spatial triad, in particular to address the interrelation of power, identity, and materiality Steyaert, 2012, 2013;Burrell and Dale, 2003;Dale, 2005;Dale and Burrell, 2008;De Vaujany and Vaast, 2013;Dobers and Strannegård, 2004;Harding, 2004, 2008;Hancock and Spicer, 2011;Hernes, 2004;Kingma, 2008;Spicer, 2009;Spicer and Taylor, 2006;Taylor and Spicer, 2007;Wapshott and Mallett, 2012;Wasserman and Frenkel, 2011;Watkins, 2005;Yeung, 1998;Zhang et al, 2008;Zhang and Spicer, 2014). For example, studies have shown how the materiality of space influences the construction of selves through forms of organizational oppression and control (Ford and Harding, 2008), analyzing both the power of aesthetically enchanting architectures (Hancock and Spicer, 2011), and the aesthetic strategies of workers to resist space-driven identity regulation (Wasserman and Frenkel, 2011).…”
Section: Lefebvre's Spatial Triad and Its Translation In Organizationmentioning
confidence: 99%
“…Figuratively speaking, an object may be wrapped up and transported, reaching its destination almost untouched, whereas an object that travels the world will be marked and transformed by its encounters along the way. As Dobers and Strannega˚rd (2004) have shown in their travelogue of an artefact, a 'cocoon', the worldwide tour and success of the artefact depended on its transformation due to continuous recontextualisation. It was not the initial brilliant idea that made the cocoon a success around the world, but the ongoing revision of it.…”
Section: To Travel the Worldmentioning
confidence: 99%